Eco-friendly Green Synthesis and Characterization of Silver Nanoparticles Derived from Murraya koenigii Leaves Extract - Ashtaputrey, S.D.; Ashtaputrey, P.D.; Rathod, Gunjan (Asian Journal of Chemistry, 2017)
Eco-friendly green synthesis of silver nanoparticles (AgNPs) was carried out using leaves extracts of plant Murraya koenigii (curry leaves) and 1 mM silver nitrate solution. During this synthesis the leaf extract works as a reducing agent. The characterization of silver nanoparticles was carried out using UV-visible spectra, scanning electron microscopy and FTIR. The characteristic surface plasmon resonance (SPR) absorption peak was found at 340 nm in UV-visible spectra confirms the formation of silver nanoparticles. The morphological study from SEM images gave an idea about the formation of asymmetrical spherical shape silver nanoparticles which are rested on the leaves extract residue. FTIR spectrum clearly suggested the green synthesis of silver nanoparticles initiated by the leaves extract. This green synthesis method is quite fast, easy to perform and does not involve the use of any harmful and costly chemicals.